Association of periodontal pocket area with type 2 diabetes and obesity: a cross-sectional study - Yoshihiro Ogawa; Isao Minami; Kohei Takeda; Koji Mizutani; Daisuke Kido; Risako Mikami; Kuniha Konuma; Natsumi Saito; Hiromi Kominato; Shu Takemura; Keita Nakagawa; Yuichi Izumi; et al. (BMJ Open Diabetes Research & Care)
Introduction The aim was to investigate the relationship of full-mouth inflammatory parameters of periodontal disease with diabetes and obesity.Research design and methods This cross-sectional study conducted diabetes-related examinations and calculated periodontal inflamed and epithelial surface area (PISA and PESA) of 71 Japanese patients with type 2 diabetes. Multiple linear regression analyses were performed to evaluate associations between PISA or PESA and diabetes and obesity parameters.Results Median value of body mass index (BMI), hemoglobin A1c (HbA1c) level, fasting plasma glucose (FPG) level, and visceral fat area (VFA) were 25.7 kg/m2, 9.1%, 151 mg/L, and 93.3 cm2, respectively. PISA and PESA were significantly associated with HbA1c after adjusting for age, sex, BMI, smoking status, and full-mouth plaque control level (PISA: coefficient=38.1, 95% CI 8.85 to 67.29, p=0.001; PESA: coefficient=66.89, 95% CI 21.44 to 112.34, p=0.005). PISA was also significantly associated with the highest FPG tertile (>175 mg/dL) after adjusting for confounders (coefficient=167.0, 95% CI 48.60 to 285.4, p=0.006). PISA and PESA were not significantly associated with BMI or VFA.Conclusion PISA was associated with FPG and HbA1c, but not with obesity parameters, independent from confounders such as full-mouth plaque control level in patients with type 2 diabetes.